2009
DOI: 10.1590/s1806-37132009001100015
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento endoscópico de fístulas da árvore traqueobrônquica com dispositivos para a correção de defeitos do septo interatrial: resultados preliminares

Abstract: fistulas ranges from 0 to 28%, (1,2) and the mortality rate ranges from 16 to 72%. Non-neoplastic tracheoesophageal fistulas can be congenital, (4,5) iatrogenic (6) or related to thoracic trauma. Once such a fistula has been diagnosed, surgical closure is formally indicated. IntroductionFistulas in the tracheobronchial tree have a multifactorial etiology and present a variable incidence in the literature. The related morbidity and mortality are high. Bronchopleural fistulas usually result from surgical procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Following our initial report using AD to seal BPF [15,16], several other groups [24,25,26] have described their experience with this technique. Scordamaglio et al [24] described a 53-year-old patient who underwent right upper lobectomy due to aspergilloma with hemoptysis and developed BPF at the right upper lobe stump. The patient was successfully treated by bronchoscopic closure of the fistula using an AD and was doing well at the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Following our initial report using AD to seal BPF [15,16], several other groups [24,25,26] have described their experience with this technique. Scordamaglio et al [24] described a 53-year-old patient who underwent right upper lobectomy due to aspergilloma with hemoptysis and developed BPF at the right upper lobe stump. The patient was successfully treated by bronchoscopic closure of the fistula using an AD and was doing well at the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, Scordamaglio et al and Gulkarov et al found successful closure of BPFs with ADs in all 3 patients, with an asymptomatic 6-month follow-up. 11,12 It is suggested that the placement of AD induces granulation tissue formation around the device, allowing for complete closure of the fistula without compromising airway patency. Using the same techniques as those for the repair of BPFs and ASDs, AD can be used for the treatment of TEFs.…”
Section: Discussionmentioning
confidence: 99%
“…The rational for bronchoscopic treatment of BPF in patients whose clinical condition precludes surgical correction is the fact that the placement of an occluder in the bronchial stump results in rapid improvement of symptoms. In a previous study conducted by our group, we reported our experience with the bronchoscopic treatment of fistulas ( 14 - 16 ) .…”
Section: Discussionmentioning
confidence: 99%